2020
DOI: 10.3390/su12229679
|View full text |Cite
|
Sign up to set email alerts
|

Structural Performance of Shear Loaded Precast EPS-Foam Concrete Half-Shaped Slabs

Abstract: Precast concrete elements provide a feasible way to expedite on-site construction; however, typical precast components are massive, making their use particularly undesirable at construction sites that suffer from low load-bearing capacity or have swelling soils. This research aims to develop an optimal lightweight expanded polystyrene foam concrete (EPS-foam concrete) slab through a consideration of various parameters. The precast EPS-foam concrete half-shaped slabs were prepared with a density and compressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…While in other studies the EPS-foam concrete showed a reduction in self-weight of up to 20% [21], EPS concrete from this study achieved an almost 50% reduction. Therefore, the use of EPS can once again be considered as an option for the creation of a reliable lightweight concrete.…”
Section: Density Of Concretecontrasting
confidence: 68%
“…While in other studies the EPS-foam concrete showed a reduction in self-weight of up to 20% [21], EPS concrete from this study achieved an almost 50% reduction. Therefore, the use of EPS can once again be considered as an option for the creation of a reliable lightweight concrete.…”
Section: Density Of Concretecontrasting
confidence: 68%
“…Several factors affect the concrete thermal conductivity [55]. For instance, the type of aggregate [56,57], the properties of cementitious materials [58][59][60][61][62][63][64][65][66], moisture content [67,68], design buildup [69][70][71][72][73][74], temperature [75,76], concrete density [12,[77][78][79][80], etc. The measurement of concrete thermal conduction is divided into steady-state and transient methods [81].…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…To date, massive research has been conducted on structural OPS concretes [ 45 , 46 , 47 , 48 , 49 , 50 ], where the inclusion of palm oil industry wastes has shown excellent overall concrete properties and durability while incorporating extra advantages of load-carrying characteristics despite being low mass. Moreover, quarry dust (QD) from the mining industry has been identified as useful material for the concrete matrix, attributing to some research on its potential as an aggregate replacement [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. So, QD can be reused in concrete as a building material to reduce the by-product waste disposal into the surrounding environment since severe health issues can be one of the consequences [ 58 ].…”
Section: Introductionmentioning
confidence: 99%